Investigating occupation as frame for planning and developing agricultural extension VET skills for climate resilience: cross-case analysis of Alice, South Africa, and Gulu, Uganda - Muhangi, Sidney (Rhodes University, Faculty of Education, Department of Secondary and Post School Education)
In sub-Saharan Africa and most of the Global South, climate change is challenging work and livelihoods for smallholder farmers who depend on rainfed farming, demanding climate resilience. Smallholder agriculture in Africa remains a mainstay for most economies and livelihoods, including South Africa and Uganda. My firsthand experience in Uganda as a subsistence farmer revealed the vitality of extension services to farmers. Participating in VETAfrica 4.0, a VET skill planning project, sparked my interest in examining the adequacy of 'Occupation' as a skills planning tool for addressing contemporary climate change challenges faced by extension officers and farmers, with implications for skills development. This research sought to answer the question: What is the theoretical and practical history and current constitution of the agricultural extension officer occupation as a mediating unit of intervention for VET skills planning, and is it adequate for climate resilience? The study addressed five objectives. First, the study undertook a historical review of occupation as a mediating unit of intervention for skills planning. Secondly, the study examined current descriptions of the extension occupation as used for skills planning in Africa. Thirdly, in order to better understand the operationalisation of this skills planning instrument, the study examined aspects of skills development, specifically how VET preparation for extension work was taking place in response to the need for climate resilience through a curriculum review and the experiences and related work activities of extension services actors. The study also reviewed agricultural extension and VET policy, and labour market data for its responsiveness to climate resilience. In response to the findings of Objectives 1-4, a fifth objective was developed to offer expanded possibilities for a mediating unit of intervention for skills planning and development relevant to climate resilience in agricultural extension, as this appeared to be needed. To develop the study, I drew on the Social Ecosystems Model (SEM) for skills, which raises the issue of mediation in skills development. I also drew on Cultural-Historical Activity Theory (CHAT) to help theorise the mediation in the SEM for skills, where different activity systems (policy, training and extension, farming) were present. This framework allowed me to probe how these activity systems were mediating climate-resilient skills development with/for extension services (or not). Empirical data was produced through secondary and primary data, generated in two case study contexts using a cross-case design. Documentary analysis involved analysing policy documents, study curricula and historical literature to develop an understanding of historical sociology of occupation as a skills planning mediating unit and insight into contemporary understanding of how occupational frameworks are structured and deployed. Analysis was undertaken in two stages; firstly, through in-depth cases of occupation as mediating unit of intervention for skills planning, and aspects of skills development as influenced by this as influenced by this mediating unit (Chapter 5 and 6). This offered a first layer of analysis and insights into temporality, verticalities, mediation and horizontalities in the SEM for skills in each case. Secondly, abduction was undertaken to build models of the SEM for skills as found in each of the two countries using the SEM and CHAT analytical tools (Chapter 7), showing the need for skills planning tools that are more closely related to and relevant to the contexts of skills development. Findings revealed insights into the SEM for skills related to ecological time, notably a mismatch between the cultural-historical time of occupational skills planning and development, and the temporal demands for climate resilience. Historical analysis the deep rootedness of occupations and occupational structures in colonial histories and traditions, going back as far as the medieval era, with current occupations still bearing features of ancient occupational guild practices and hence not adequately responsive to climate change, affecting the SEM for skills in both cases and producing contradictions. Analysis further revealed that contemporary agricultural extension in Africa is decentralised and pluralistic, with few extension-related policies employed underdeveloped. Labour market in both South Africa and Uganda are not adequately orientated to climate resilience and fail to include climate resilience expertise, despite a need for this amongst farmers and by policy, revealing contradictions between various policy activity systems, which are not adequately facilitating. Empirical findings from study sites revealed that VET preparation for extension work lacks responsiveness to climate resilience within the skills ecosystem. Consequently, extension officers lack expertise in climate resilience, which is an increasing demand expressed by farmers and other horizontal activity systems in the SEM for skills. Through a more complex understanding of the extension officer occupation and its development in skills ecosystem in Africa, the study proposes a broader mediating unit of intervention for skills planning than that of 'occupation' only. The mediating unit of intervention put forward for skills planning is a workstream mapping approach for climate resilient extension training in VET. This planning approach has implications for skills development viewed as work, learning and living involving more than one activity system in the skills development landscape, thus also broadening the approach to VET. The study concludes with recommendations to further test this approach. Finally, it makes recommendations that can inform: 1) curriculum innovation, 2) extension practice, 3) policy, and 4) research.
Keywords: Agricultural extension work -- South Africa Alice; Agricultural extension work Uganda Gulu; Agricultural extension workers; Climate resilience; Skills development; Climatic changes